2001
DOI: 10.1038/sj.jim.7000088
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genotypic characterization of Cryptosporidium species and isolates

Abstract: Recent outbreaks of cryptosporidiosis from contaminated water supplies have led to a need for the detection of Cryptosporidium oocysts from various hosts and contaminating sources. The presence of nonpathogenic species or strains of Cryptosporidium is important for diagnostic purposes as there is a potential for false- positive detection of pathogenic parasites. The present review focuses on phenotypic differences and recent advances in genotypic analyses of the genus Cryptosporidium with an emphasis on detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Several review articles have concluded that the degree of sequence divergence is difficult to interpret in a taxonomic context (Carreno et al 2001;Kunz 2002). Nevertheless, SSU rRNA gene sequences have been widely used in searching for evidence of distinct species as well as inferring phylogenetic relationships within genera.…”
Section: Discussionmentioning
confidence: 99%
“…Several review articles have concluded that the degree of sequence divergence is difficult to interpret in a taxonomic context (Carreno et al 2001;Kunz 2002). Nevertheless, SSU rRNA gene sequences have been widely used in searching for evidence of distinct species as well as inferring phylogenetic relationships within genera.…”
Section: Discussionmentioning
confidence: 99%
“…Taxonomically, the 11 following species are known : C. parvum, C. wrairi, C. meleagridis, C. saurophilum, C. felis, C. canis, C. baileyi, C. muris, C. andersoni, C. serpentis, C. nasorum [3,7,8]. Cryptosporidium parvum has been considered to be the only species that infects immunocompetent humans [5,9].…”
Section: Introductionmentioning
confidence: 99%
“…Several species are now recognized within the genus Cryptosporidium, a protozoon associated largely with enteric infections in all classes of vertebrates (5,7,13,14,25,26). Mammals are commonly infected by either Cryptosporidium parvum (intestinal) or Cryptosporidium muris (gastric).…”
mentioning
confidence: 99%